2001
DOI: 10.1258/1357633011936868
|View full text |Cite
|
Sign up to set email alerts
|

The potential of telemedicine: barriers, incentives and possibilities in the implementation phase

Abstract: Between 1998 and 1999, the Swedish Institute for Health Services Development (Spri) evaluated three applications in which specialist competence was being accessed via telemedicine. The results indicated that these kinds of application can be cost-effective in an organization well adapted to new technology and that telemedicine can improve continuity of care for patients. However, the new technology was seldom supported by the old organization and better education and technical support are needed. In a study ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…It is interesting to note that the respondents to the present survey were positive about these services prior to implementation. Although incentive and remuneration is a possible barrier to implementation 11 only 30% of respondents reported that it would be a limitation to their practice. In addition, organizational patterns and technological challenges are also considered to be obstacles to successful implementation.…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to note that the respondents to the present survey were positive about these services prior to implementation. Although incentive and remuneration is a possible barrier to implementation 11 only 30% of respondents reported that it would be a limitation to their practice. In addition, organizational patterns and technological challenges are also considered to be obstacles to successful implementation.…”
Section: Discussionmentioning
confidence: 99%
“…It can be expected that, as system use grows, so too will any savings, benefits and overall sustainability 3 . Evaluation activity to date has shown (not surprisingly) that where there is strong senior management support, and management interest in increasing the usage and developing a range of telehealth services, the prospect of success is greater; this has also been noted elsewhere 15 , although, as Bashshur has observed, such support is not always available 16 . In WA, where funding has ceased for individual projects, regional managers have continued the funding of services and support staff.…”
mentioning
confidence: 86%
“…New management priorities and organizational structures may be necessary for the benefits of telemedicine to be realized, including substantial investments in training in these new technologies for physicians and nurses. 11 The 2 factors that may be the biggest barriers to provider adoption and utilization are inadequate provider training (especially when the equipment installed includes features that are more complex and sophisticated than necessary) and the role of the provider as the gatekeeper to telemedicine access. 9 The direct involvement of providers in the development of disease-specific telemedicine systems greatly enhances their acceptance and adoption, but there are few published studies of failed telemedicine implementations to quantify the extent to which provider buy-in may be essential.…”
mentioning
confidence: 99%